Estimation of Online learning Challenges in Rural Areas During a Pandemic with Linear Regression - Muhammad Marizal; Diniya Diniya; Sarina Fadila H (Jurnal Sains Matematika dan Statistika, 2022)
The Covid-19 pandemic has changed the behavior of life today, including the formal learning process that is carried out online. There are many challenges faced by students in following the pattern of the online learning system. Students who live in rural areas or in non-urban areas are students who experience greater challenges. The challenges analyzed in this research are physical, psychological, family and community factors on school policies. It was found that the factors that greatly influence school policy are family and community factors. Furthermore, these factors will be modeled so that they can assist schools in establishing an appropriate policy. This model can also describe in general about online-based learning for non-city areas during the covid-19 pandemic